Increased intra-abdominal haemorrhage after thoracic endovascular aortic replacement in patients with concomitant blunt aortic injuries and abdominal trauma: a National Trauma Data Bank analysis. (4th October 2022) - Lu, Yu-Chieh; Yu, Sheng-Yueh; Fu, Chih-Yuan; Bajani, Francesco; Bokhari, Marissa; Mis, Justin; Poulakidas, Stathis; Bokhari, Faran
Abstract: OBJECTIVES: The role of thoracic endovascular aortic replacement (TEVAR) in patients with concomitant blunt thoracic aortic injury (BTAI) and blunt abdomen trauma (BAT) was evaluated using nationwide real-world data. The risk of post-TEVAR abdominal haemorrhage was studied. METHODS: Patients with BTAI and BAT in the National Trauma Data Bank were retrospectively studied. Propensity score matching was used to evaluate the effect of TEVAR in delayed abdominal surgeries for haemostasis and the delayed need for blood transfusion. A multivariable logistic regression analysis was used to evaluate the independent risk factors for delayed intra-abdominal haemorrhage in these patients. RESULTS: A total of 928 concomitant BTAI and BAT patients were studied (TEVAR versus non-TEVAR, 206 vs 722). After a well-balanced propensity score matching analysis, patients who received TEVAR had significantly more delayed abdominal surgeries for haemostasis (7.7% vs 4.5%, standardized mean difference = 0.316) and delayed need for blood transfusion (11.6% vs 7.1%, standardized mean difference = 0.299) than those who did not. The multivariable logistic regression analysis showed that TEVAR increased the need for delayed abdominal surgeries (odds ratio = 2.026, P = 0.034). Among the patients who underwent TEVAR, the patients with delayed abdominal surgeries for haemostasis had a significantly higher proportion of severe abdominal injury (abdominal Abbreviated Injury Scale score of 4 or 5) than patients without delayed abdominal surgeries for haemostasis (31.6% vs 15.5%, P = 0.038). CONCLUSIONS: Patients with concomitant BTAI and BAT had a higher risk of intra-abdominal haemorrhage after TEVAR, especially patients with severe abdominal trauma. Abstract : Blunt thoracic aortic injury (BTAI) is considered a high-energy trauma and is usually associated with other accompanying injuries, such as intra-abdominal injuries (29%) [1].